Pengolahan Limbah Rumah Tangga Menjadi Eco Enzyme Di Lingkungan Perumahan Ujung Residence - Ridho Muarief; Muhyiddin Aziz; Priyanto Priyanto; Hifzhan Frima Thousani; Intan Yuliana; Ina Syarifa; Agustinus Doedyk Setiyawan; Prasyetyo Yekti Utomo (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2023)
Eco-enzyme is one of the potential organic waste processing technologies in the future. This community service activity aims to provide training on eco-enzyme household waste management in the Ujung Residence housing environment and youth groups in Ngujung Village, Maospati District, Magetan Regency. This activity begins with the dissemination of technology and the use of eco-enzymes through interactive lectures and discussions, followed by demonstrations of eco-enzyme production by the resource persons. The assessment is carried out according to a process that includes the presence of participants, enthusiasm/enthusiasm and response to training activities, as well as ecological enzyme products produced by the participants' production houses. The results of the service show that the training activities have been able to improve the knowledge and skills of the community in processing organic waste into ecological enzymes. The results of the evaluation showed that the response, enthusiasm, acceptance, presence and participation of the community in the training activities were very good. The eco-enzyme product produced by the participants was considered successful if it met certain criteria, namely brown color, distinctive fruity odor with a slight alcohol aroma, acidic pH (3-4) and free of mold or maggots.